Usuń nawiasy i wykonaj redukcję wyrazów podobnych . :

( ⅗ m² + ⅔ n² + 6 ) + ( -⅓ m² - ⅔ n² - 2 ⅗ ) =

( 0,5 xy² - 1,2 y² + 5 ) + ( -0,8 y² - 2,5 xy² - 2⅛ ) =

_____________________________________________________
klasa 1 gim. str. 152 zad. 6 , (przykład b.,c. )

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T19:35:55+01:00
A) ⅗ m² + ⅔ n² + 6 - ⅓ m² - ⅔ n² - 2 ⅗ = 9/15 m²-5/15m²+5i5/5-2i3/5 = 4/15m² + 3i2/5

b) 0,5 xy² - 1,2 y² + 5 - 0,8 y² - 2,5 xy² - 2⅛ = 0,5xy² - 2,5xy² - 1,2 y² - 0,8y² + 5-2⅛ = -2xy²-2y²+4i8/8 - 2⅛ = -2xy²-2y²+2i7/8
2 4 2
2010-02-04T19:40:13+01:00
1. ⅗ m² +⅔ n² + 6 - ⅓ m² - ⅔ n² - 2 ⅗-= 9/15m² - 5/15 m²- 3⅖ = 4/15m² - 3⅖
2.0,5 xy² - 1,2 y² + 5 - o,8y² - 2,5 xy² - 2⅛ = -2 xy² - 2 y² + 2⅞
1 2 1